60h=40+55h

Simple and best practice solution for 60h=40+55h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60h=40+55h equation:


Simplifying
60h = 40 + 55h

Solving
60h = 40 + 55h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-55h' to each side of the equation.
60h + -55h = 40 + 55h + -55h

Combine like terms: 60h + -55h = 5h
5h = 40 + 55h + -55h

Combine like terms: 55h + -55h = 0
5h = 40 + 0
5h = 40

Divide each side by '5'.
h = 8

Simplifying
h = 8

See similar equations:

| 10k-1=-6k-43 | | -10w-3-2.5w+20=67 | | 2x+61+4x+32=105 | | 2x+3y+3x=15 | | 13-3x-=8x+4-11x | | 5/3x-10=1/3x | | 3(x-15)-13=x+1 | | 2(24)+2y=-56 | | H=-16t^2+1000t | | f(x)=2.15(2x-4x-6) | | 2x^2+12k=-18 | | 7+3x(1-x)=5-2(3-4x) | | x(2x-2)=4 | | 5(2x-10)(x+3)=0 | | abs(5x+2)-7=-3 | | x(2x-2)=0 | | 20x-2=18-4 | | 50+6x+27=3x+86 | | h(t) = -16t2 + 32t + 40 | | 6x-10x=4 | | (5w-8)(1-w)=0 | | 6x=5x+2(x-1)-x+b | | (x-4)-(3-2x)=(3x+4)-(6+x) | | ln(5x-12)=9 | | Y-a=26 | | n^2-2n-3=6 | | x^2+6x=130 | | (3+2i)(3+2i)=0 | | 10m=k^2 | | 4g+3=23 | | X^2+5-104=0 | | 3n=30-3 |

Equations solver categories